Coupling characteristics of construction safety risk and complicated factors of metro station: a case study of Ningbo - Ping Wu; Jiamin Huang; Yinqi Chen; Jun Zhang; Yidong Xu (Journal of Asian Architecture and Building Engineering, 2025)
This paper investigates the coupling relationship and degree of complex factors corresponding to the metro station construction in the Ningbo region. To this end, the interpretative structural modeling (ISM) method, a structural interpretation model, is utilized to develop the coupling connection network of construction risk factors. Moreover, the cloud model theory and coupling degree model are used to calculate the risk factor coupling degree within and between the construction safety risk subsystems. The analysis indicates that the coupling degree of risk factors within and among subsystems is notably high, falling into categories characterized by high coupling and strong coupling. It is also found that the entire coupling system is in a state of high-strength coupling. Therefore, during the construction process, the coupling impact of risk factors must be avoided, and risk factors must be prevented from further developing into risk events. The quantitative evaluation of the coupling degree between and among risk factor subsystems in this study provides a reference for project risk evaluation and facilitates the development of subsequent construction safety measures.